PENGARUH PELAKSANAAN PROSEDUR KERJA DAN PENGAWASAN MANDOR TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PT. PERKEBUNAN NUSANTARA V SEI-BUATAN - Yun Tri Asih; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The study aims to determine the effect of implementation of work procedures and supervision of the foreman on the performance of employees of production at PT. Perkebunan Nusantara V Sei-Buatan. Working procedure as independent variable (X1), Overseer supervision as independent variable (X2). While employee performance as a dependent variable (Y). Method in this research is descriptive and quantitative by using program of SPSS 16, where the sample used is employee of production that is 63 person conducted by census and technique of collecting data through questioner. The results of analysis using the validity test, reliability test, test determination, simple linear regression test, multiple linear regression test, t test and F test. So it can be concluded that the implementation of work procedures significantly affect the performance of employees of production at PT. Perkebunan Nusantara V Sei-Buatan, supervision of the foreman has a significant effect on the performance of employees of the production of PT. Perkebunan Nusantara V Sei-Buatan, and the implementation of work procedures and supervision of the foreman significantly affect the performance of employees of production PT.Perkebunan Nusantara V Sei-Buatan.Keywords: Human Resource Management, Work Procedure, Supervision, Performance